UAI case: An uCASE-CL model implementation - Nicolas Battaglia; Neil Carlos; Roxana Martinez; Marcelo De Vincenzi (OmniaScience, 2019)
The new models of teaching and learning have their focus on technology, especially on issues related to ubiquity. The impact of ICT in education generates new learning opportunities: the mobile or ubiquitous, which open new doors to technological environments that allow students to learn at any time and place, providing, in addition, tools that give the possibility to perform collaborative work and learning. The integration of a ubiquitous virtual teaching and learning environment with collaborative work forms the Ubiquitous Computer Supported Collaborative Learning model. What has been mentioned before allowed us to understand the importance of making a specification of this model that provides the possibility of using a tool for professional use in the Software Engineering during the teaching and learning processes, including the specific activities of evaluation and monitoring of works. These tools, called Computer-Aided Software Engineering, must be an active part of the uCSCL model. This integration, forms the model proposed in our work, called uCASE-CL. A prototype of the implementation of the model was developed, which we have called UAI Case. This solution is a proposal to cover the need to have tools that can be used in the teaching of the SE, and which allow the student to acquire and strengthen the academic learning.